PROFIL KETERAMPILAN TEKNIK DASAR BERMAIN BOLA BASKET PADA TIM PUTRA MAN 2 MODEL KOTA PEKANBARU - Putra, Alfino; Ramadi, Ramadi; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The research is intendeed too see profil and the level of basic tchnique skilll in olaying basketball on male student of MAN 2 Model of Pekanbaru’s basketball team.The problem in this research is unachieved achievment on male student basketball team of MAN 2 Model of Pekanbaru. This research is non experiment research with advance model of one shot model wich is an approaching model that using one time data collecting on one time of session. Sample in this research is 12 students that obtained with sampling technique from population of male student basketball team of MAN 2 Model of Pekanbaru. Instrument in this research is some test on sample with reflecting ball to the wall, dribbling ball, and shooting to the basket. Processing of the data in this research using statistic procedure with percentage description analysis. The result of this research show there is no player can achieve “very good” category, 6 player (50%) with “good” category, 6 player (50%) with “enough” category, 0 player with “medium” category, 0 player with “bad” category, and 0 player with “very bad” category. With that result, 12 player as sample with average point of basic technique skill is189,3. In this point, conclution of this research is the level of basic basketball technique skill on male student of MAN 2 Model of Pekanbaru’s basketball team has category wich is enough.Keyword: Profile/position/, fundamental technique’s skill in playing basketball